Javier Milei's ideology and policy: Libertarian populism in Argentina - Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2024)
Javier Milei's disruptive political style does not appear to have changed since taking office as Argentina's president on 10 December 2023. He continues to behave, including on social media, as an aggressive, lone warrior leading a crusade. Milei's government policies are largely in line with his campaign rhetoric. In July 2024, the government scored its first negotiating successes, pushing a legislative package through parliament and reaching an economic compromise with three-quarters of the provincial governors. While the economic prospects of Argentina still remain uncertain, many of the democratic advances achieved in recent decades are currently facing significant challenges.eturn does little to change these structural incentives. Instead, Pacific allies fear challenges to the East Asian regional order, challenges that are also relevant for Europe's security and prosperity.
Keywords: 320; Javier Milei; Argentina; libertarian populism; economic prospects; La Libertad Avanza (LLA; The Freedom Advances); "new foreign policy doctrine"; femicide